A Rare Case of Rapidly Progressing Vertex Epidural Hematoma in A Child: Diagnostic Pitfalls and Management Considerations - Bangun, Kristian Gerry Raymond Sinarta; Satyarsa, Agung Bagus Sista; Niryana, Wayan (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Vertex Epidural Hematoma (EDH) is a rare condition, often caused by injury to the superior sagittal sinus or parietal bone fractures, typically involving diploic veins. It can be associated with sudden death. This case highlights a rapidly progressing vertex EDH in a child within 12 hours, despite initial mild symptoms. A 10-year-old boy sustained a head injury and experienced a 10-minute loss of consciousness. Upon arrival at Ngoerah General Hospital, his Glasgow Coma Scale (GCS) score was E4V5M6, and a head CT showed a small vertex EDH. Conservative management was started. Twelve hours later, the child reported worsening headaches and drowsiness, and his GCS decreased to E3V5M6. A repeat CT scan revealed significant hematoma expansion, prompting emergency surgery. During surgery, a linear fracture of the parietal bone was found, with approximately 60cc of hematoma due to diploic vein rupture. Post-surgery, the patients GCS improved without neurological deficits. As conclusion the Vertex EDH in children, though rare, demands careful monitoring. This case underscores the importance of early reevaluation, prompt imaging, and timely surgical intervention to avoid irreversible neurological damage